Washington Saw Works Company Golden Potlatch float, Seattle, 1912 - Pierson and Co. (1912)
The Golden Potlatch was a summer festival held in Seattle from 1911 through 1914. Organized by city boosters, it was designed to promote the area's business interests and keep newly-prosperous Seattle in the public eye after the Alaskan gold rush and the success of the 1909 Alaska-Yukon-Pacific Exposition. Organizers of the 1912 Golden Potlatch decided to give the annual parade an industrial focus. Here, a group of men and one young boy gather at the Mercantile Lumber Company float, which featured circular saw blades and a large steel plate, all made by the Washington Saw Company. The men who rode on the float hammered on the steel saws as they moved along the parade route. Writing on saw in image: Washington Saw Co. Steel Plate. 84 in. Diameter. The Weight 400 lbs. Best Steel in the World.=CHAR(13)=CHAR(13)Embossed on mat recto: Pierson & Co., Seattle Caption information source: The Seattle Daily Times, July 20, 1912. 1 photographic print mounted on cardboard: b&w; 9.5 x 7.5 in.